Prohear, Kambodscha. Eine Benchmark für das frühe Goldhandwerk in Südostasien - Reinecke, Andreas (e-Forschungsberichte des DAI, 2023)
In 2012 and 2013, the metal composition of early gold objects from 10 sites in Cambodia, Vietnam and Indonesia were analyzed by Laser Ablation-Inductively Coupled Plasma-Mass Spectrometry as part of a cooperation-project between the KAAK/DAI and the Curt-Engelhorn-Center for Archaeometry Mannheim. The basis of this project is a spectacular gold collection which was excavated between 2008 and 2011 in 32 of 76 burials at Prohear in Southeastern Cambodia. By their variety and the well documented burial context combined with archaeometrical data, the Prohear collection can be considered as a benchmark of early gold in Southeast Asia, both from the typological point of view and for the discussion of early exploited deposits and trade networks in this region. The results give such important suggestions for the archaeological interpretation of the early gold’s origin and the beginning of the goldsmith craft that we want to expand the sample series in the future completed by the analyzing of deposit samples in this region.